(untitled) (Modern education and development, 2025)
Effective operation of crankcase hydraulic excavators in a hydraulic system is significantly affected by temperature conditions. In the hydraulic system, a sharp increase in the temperature of the working fluid or of the parts on which the packing gaskets are applied leads to burning of the packing gaskets, resulting in a loss of their elasticity and an increase in their hardness.